Policy-Sealed Data: A New Abstraction for Building Trusted Cloud Services - Santos, Nuno; Rodrigues, Rodrigo; Gummadi, Krishna; Saroiu, Stefan (21st USENIX Security Symposium, 2012)
Accidental or intentional mismanagement of cloud software by administrators poses a serious threat to the integrity and confidentiality of customer data hosted by cloud services. Trusted computing provides an important foundation for designing cloud services that are more resilient to these threats. However, current trusted computing technology is ill-suited to the cloud as it exposes too many internal details of the cloud infrastructure, hinders fault tolerance and load-balancing flexibility, and performs poorly. We present Excalibur, a system that addresses these limitations by enabling the design of trusted cloud services. Excalibur provides a new trusted computing abstraction, called policy-sealed data, that lets data be sealed (i.e., encrypted to a customer-defined policy) and then unsealed (i.e., decrypted) only by nodes whose configurations match the policy. To provide this abstraction, Excalibur uses attribute-based encryption, which reduces the overhead of key management and improves the performance of the distributed protocols employed. To demonstrate that Excalibur is practical, we incorporated it in the Eucalyptus open-source cloud platform. Policy-sealed data can provide greater confidence to Eucalyptus customers that their data is not being mismanaged.